PENGARUH FAKTOR-FAKTOR RIIL EKONOMI TERHADAP PDRB PERTANIAN INDONESIA - Tarmizi Abbas; Nurhayati M (Jurnal Ekonomi Pertanian Unimal, 2021)
This study analyzed the effects of government expenditure, investment, and  labor  on  the Gross  Regional  Domestic  Product  (GRDP)  of  the agricultural sector in all provinces in Indonesia using panel data for four years (2015 - 2018). The model used was a Panel Data Regression. The results showed that Government Expenditure, Investment positively influenced,   and   Labor   negatively   influenced   the   GRDP   of   the Agricultural Sector, and these three variables significantly influenced the GRDP of the Agricultural Sector in Indonesia.